Exploring Chemistry Confusions and Misconceptions in Nepalese Secondary Education - Subedi, Rishi Ram (Interdisciplinary Research in Education, 2024)
This study investigates the confusions and misconceptions in chemistry of ninth and tenth graders in Nepal. The primary objectives were to identify misconceptions in various areas of chemistry, determine their sources, and understand teachers' perceptions of these misconceptions. A concurrent mixed-method research design was employed, utilizing questionnaires and interviews for data collection. A random sample of 120 students from Grades 9 and 10 participated in the study. The findings revealed significant misconceptions in areas such as chemical reactions and stability, chemical equations, acids, bases and salts, and the periodic table. The main sources of these misconceptions were identified as common sense, textbooks, and teachers. The study highlights the importance of addressing these misconceptions to improve chemistry education. It provides valuable insights for future research, aiding in the planning and development of theoretical and conceptual frameworks to better understand and mitigate misconceptions in chemistry education.